Synthesis and characterization of novel HMPM bridged ball-type metallophthalocyanines, and their DFT studies and electrochemical performance as supercapacitor electrodes - Kocyigit, Nilufer; Arvas, Melih Besir; Yazar, Sibel; Acar-Selcuki, Nursel; Sahin, Yucel; Ozer, Metin; Bekaroglu, Ozer (ELSEVIER SCIENCE SA, 2023)
Novel 4, 4'-((((2-(3, 4-dicyanophenoxy)-5-methyl-1, 3-phenylene) bis (methylene)) bis (4-methyl-3, 1-phenylene)) bis (oxy)) -bridged ball-type phthalocyanines were achieved from 4, 4' -((((2-(3, 4-dicyanophenoxy)-5methyl-1, 3-phenylene) bis (methylene)) bis (4-methyl-3, 1-phenylene)) bis (oxy)) diphthalonitrile through appropriate transition metal (II) acetate salts in 2-dimethylaminoethanol. The new tris-phthalonitrile precursor was achieved from 3,3'-((2-hydroxy-5-methyl-1,3-phenylene) bis (methylene)) bis (4-methylphenol), and 4nitrophthalonitrile with the presence of catalyst potassium carbonate in dimethylformamide at 50.C. The structural verification of the compounds was accomplished by proton-nuclear magnetic resonance, matrixassisted laser desorption/ionization time-of-flight mass, infrared, and ultraviolet-visible spectroscopic methods. The BTCuPc electrode material exhibited a specific capacitance of 265 F.g 1 at a scan rate of 5 mV.s 1 in 3.0 M KCl aqueous electrolyte. In addition, a wide operating potential range (1.5 V) was achieved in the aqueous electrolyte.
Keywords: Ball-type phthalocyanine; Synthesis; Supercapacitor electrode; Computational studies; SENSING PROPERTIES; POLYPYRROLE; Materials Science; Physics; Polymer Science